10 simple rules for experimental design in ecology - Saini, Neha (PeerJ Preprints, 2016)
This article contains proposed guidelines for ensuring proper experimental design in ecology. In a sequential fashion, it is important to begin with stating a hypothesis, followed by clearly defining terms and choosing appropriate samples and parameters. Following the tips and guidelines in order will help guide the researchers thought process when designing an ecological experiment. Consult the listed citations for in-depth explanations when required. The rules may be generalized to other fields of science.
Keywords: Lortie; experimental design; OUFB; best practices; environmental science; ecology; general science; UCNRS; Kenneth S. Norris Rancho Marino Reserve; ecodreamers